2015
DOI: 10.1097/qai.0000000000000455
|View full text |Cite
|
Sign up to set email alerts
|

“It's All About Making a Life”

Abstract: The pathway to sex work followed a similar pattern for many study participants who left their rural homes for Kumasi in search of economic opportunity. While adolescents who sell sex appear to be abundant in Kumasi, they have been missed by HIV prevention and harm reduction programming. The findings from this study informed the design and implementation of a young female sex worker peer educator pilot program. Key elements of that program are presented, and recommendations for future program evaluation are mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The risk of violence and unprotected sex with alcohol use among FSW has been well-documented globally (Chersich et al, 2007; El-Bassel, Witte, Wada, Gilbert, & Wallace, 2001; Li, Li, & Stanton, 2010; Mbonye, Rutakumwa, Weiss, & Seeley, 2014; Onyango et al, 2015; Wechsberg, Luseno, & Lam, 2005). Yet, knowledge has been limited on how FSW understand these risks within the context of their own alcohol use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of violence and unprotected sex with alcohol use among FSW has been well-documented globally (Chersich et al, 2007; El-Bassel, Witte, Wada, Gilbert, & Wallace, 2001; Li, Li, & Stanton, 2010; Mbonye, Rutakumwa, Weiss, & Seeley, 2014; Onyango et al, 2015; Wechsberg, Luseno, & Lam, 2005). Yet, knowledge has been limited on how FSW understand these risks within the context of their own alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…FSW use alcohol to facilitate sex work, and both FSW and clients often consume alcohol at the time of sex (Chersich et al, 2007; de Graaf, Vanwesenbeeck, van Zessen, Straver, & Visser, 1995; El-Bassel, Witte, Wada, Gilbert, & Wallace, 2001; Li, Li, & Stanton, 2010). FSW use alcohol to reduce their insecurities or become more comfortable when approaching potential clients (Onyango et al, 2015). Clients also often purchase alcohol for FSW prior to sex to establish the sexual transaction (Li, Li, & Stanton, 2010; Wojcicki & Malala, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the way in which YWSS sell sex is poorly understood and often excluded from the literature on FSW due to the considerable ethical considerations in including YWSS under age 18 in research [ 20 , 21 ]. Increasingly, however, there have been calls to move beyond simplistic portrayals of all underage YWSS as “trafficking victims” in order to gather data that are required for effective methods of reaching this vulnerable population, including offering services that are likely to be acceptable and taken up by YWSS, rather than driving them further underground and into higher risk situations [ 10 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most participants reported engaging in transactional sex and feeling comfortable doing so, viewing the exchange of money, gifts, and favors as a natural and positive activity. This is not surprising in a low-resource environment, given evidence from Ghana and elsewhere that young people are often persuaded or inclined to exchange sex for money or goods [ 13 , 28 , 32 , 36 , 37 ]. The Ghana Men’s Study found participation in transactional sex among MSM aged 18-35 years to be 60% in Kumasi and 65% nationwide [ 13 ].…”
Section: Discussionmentioning
confidence: 99%